VARIASI DIMENSI BRAND IDENTITY PADA CONTENT MARKETING AVOSKIN (The Commercium, 2022)
This study was initiated by the release of web series "Kisah Tiga Masa" in the official Youtube account of Avoskin, which is a type of content marketing in the form of online video advertisements. Avoskin is known as a brand that is concerned with the environment, with a green beauty idea that is funneled in the majority of its marketing content through the hashtag #LoveAvoskinLoveEarth. The purpose of this study is to determine how many brand identity dimensions are raised and the percentage of brand identity dimensions that appear in the web series. This study is a descriptive quantitative study that examines the emergence of brand identity aspects in web series. Documentation techniques were used to collect the data for this research. This results of this analysis reveal a total of five dimensions emanating from each brand identity category. The highest result, 42%, is found in the brand personality dimension, and the lowest result, 1%, is found in the organizational attribute dimension.